2014
DOI: 10.3109/02699206.2014.927000
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and production of emotions in children with cochlear implants

Abstract: The aim of this study was to examine auditory recognition and vocal production of emotions in three prelingually bilaterally profoundly deaf children aged 6-7 who received cochlear implants before age 2, and compare them with age-matched normally hearing children. No consistent advantage was found for the normally hearing participants. In both groups, sadness was recognized best and disgust was the most difficult. Confusion matrices among other emotions (anger, happiness, and fear) showed that children with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…intensity, tempo and duration. Mildner and Koska (2014) investigated bilaterally deaf children who had received CIs before age of two in terms of their ability to recognize auditory emotions. These children were compared with their NH peers of the same age (six to seven years old).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…intensity, tempo and duration. Mildner and Koska (2014) investigated bilaterally deaf children who had received CIs before age of two in terms of their ability to recognize auditory emotions. These children were compared with their NH peers of the same age (six to seven years old).…”
Section: Discussionmentioning
confidence: 99%
“…The melodicity of the speech was found to be connected to positive vocal expressions rather than to negative expression, the latter having more voice breaks, irregularities, and unpredictability (Waaramaa, 2015). Mildner and Koska (2014) suggested that HI children benefit from early implantation and regular auditory/oral-based therapy, as this combination enables these children to express and perceive emotional content that is comparable with their NH peers. Today, when possible, both ears are implanted for the children with hearing loss during their first year or at the age of one in order to enhance speech and localization perception.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to such cross-sensorial and unisensorial effects, hearing impairment could compromise multisensory integration, in relation to its onset, etiology, and severity, leading the patient to rely only or predominantly on the visual modality in communication, including emotional perception and expression (Mildner and Koska, 2014). In fact, for 92% of children with cochlear implant (CI), perception was dominated by vision when visual and auditory speech information conflicted (Schorr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Auditory–visual associations may be an important strategy for improving speech decoding and emotion recognition under conditions of spectral degradation. Integration of multisensory information is an automatic process that emerges early in life ( Mildner & Koska, 2014 ). Infants are capable of using multimodal information in a range of perceptual and cognitive tasks (e.g., Bahrick & Lickliter, 2000 ; Flom & Bahrick, 2010 ) and are more inclined to perceive speech multimodally than children ( Burnham & Dodd, 2004 ) who later demonstrate age-related improvement in these abilities extending into adulthood ( Jerger, Damian, Spence, Tye-Murray, & Abdi, 2009 ; Sommers, Tye-Murray, & Spehar, 2005 ).…”
mentioning
confidence: 99%